(3fgGjI GdCMcGe aj eYQaI GdCMcGes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdeJbOS Yf eTGQcI GdeecfGJ HhLhH eGgjJg, GdeJfRg Yf eTGHgI GdeNdhbGJ HLdGd UeOGfjJg (B... (3CeG HYO, agPG cJGH (B... (3dNUJ ajg aJGhi GdEeGejI Ydi hLg GdGNJUGQs
(3BNQgG (B:s
(3BNQgG(B: (3Ydi GdPgH hGdaVI dUaGA LhgQgG hGJaGb aj GdHdOGf GdeaQWI aj GdMQ Ohf GdeHGOQI hGdeYJOdI dVYa JCKjQ GdTeS ajgG, hdG aQb Hjf Cf jbY Pdc bUkOG (B... (3aj GdChGfj HGdeWHbI hZjQgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 227s
(3GdPQjYI, L (B24: 239s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis